1993
DOI: 10.1002/hlca.19930760625
|View full text |Cite
|
Sign up to set email alerts
|

8‐Aza‐2′‐deoxyguanosine and Related 1,2,3‐Triazolo[4,5‐d]pyrimidine 2′‐Deoxyribofuranosides

Abstract: The synthesis of 8-azaguanine N9-, N8-, and N7-(2'-deoxyribonucleosides) 1-3, related to 2'-deoxyguanosine (4), is described. Glycosylation of the anion of 5-amino-7-methoxy-3H-l,2,3-triazolo[4,5-d]pyrimidine (5) with 2-deoxy-3,5-di-O-(4-toluoyl)-a -D-erythro -pentofuranosyl chloride (6) afforded the regioisorneric glycosylation products 7a/7b, 8a/8b, and 9 (Scheme 1 ) which were detoluoylated to give 10a, lob, l l a , l l b , and 12a. The anomeric configuration as well as the position of glycosylation were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
20
1
Order By: Relevance
“…[72] Ribosides and deoxyribosides of 8-azaDaPur have been synthesized many years ago, [73,74] but their fluorescence properties were not examined until recently. We have found that enzymatically generated N9-, N8-, and N7-β-d-ribosides of 8-azaDaPur are highly fluorescent, [75] with yields of ca.…”
Section: 6-diamino-8-azapurine and The Corresponding Ribosidesmentioning
confidence: 99%
“…[72] Ribosides and deoxyribosides of 8-azaDaPur have been synthesized many years ago, [73,74] but their fluorescence properties were not examined until recently. We have found that enzymatically generated N9-, N8-, and N7-β-d-ribosides of 8-azaDaPur are highly fluorescent, [75] with yields of ca.…”
Section: 6-diamino-8-azapurine and The Corresponding Ribosidesmentioning
confidence: 99%
“…[17,18] Therefore, the incorporation of Z G instead of guanine into β-peptide 14helices should suppress higher aggregation due to Hoogsteen pairing of guanine. [19] In addition, the incorporation of Z G as a guanine analog into double strands diminishes the double-strand stability if guanine recognition on the Hoogsteen site is required. A comparison of guanine-and Z G-containing oligomers might allow conclusions to be drawn on the preferred guanine-pairing mode in β-peptide double strands.…”
Section: Introductionmentioning
confidence: 99%
“…The glycosylation reactions then proceeded smoothly. Nucleosides derived from sugars 13b, 13 13d, 14 and 13f 15 by virtue of lacking a protected 3¢-hydroxyl gave a mixture of anomers as anticipated. The a/b anomers were separated by chromatography and the stereochemistry determined by comparison of the 1 H NMR's to analogus purine nucleosides for the same sugars.…”
Section: Figurementioning
confidence: 83%